Efficacy and safety of Toliparibumab for the treatment of non-small cell lung cancer: a systematic review and meta-analysis - Liu, Yihao; Yang, Liangyu; Duan, Zhixuan; Cheng, Qian; Liu, Minghui; Zhang, HongBing; Zhao, HongLin (Frontiers in Oncology, 2024)
PurposeThis research intends to investigate the treatment of non-small cell lung cancer (NSCLC) using Toripalimab, focusing on its effectiveness and safety profile. Efficacy refers to the survival prognosis, while safety pertains to the occurrence of adverse events in our study. It also aims to provide reference information for neoadjuvant and postoperative therapies.MethodsUp to March 20, 2024, studies on randomized controlled trials and single-arm trials involving Toripalimab for NSCLC were sourced from the Cochrane Library, Embase, PubMed, and Web of Science databases. Data extraction and analysis were independently conducted by two researchers utilizing Stata 15.0 and R software.ResultsA total of 8 studies were analyzed, including 6 single-arm studies and 2 randomized controlled trials (RCTs). Toripalimab treatment in the RCTs showed an overall survival (OS) of [HR=0.67, 95% CI (0.53, 0.85); p=0.71]. The objective response rate (ORR) from single-arm studies was reported as [ES=0.59, 95% CI (0.36, 0.81); p<0.01], and progression-free survival (PFS) was [ES=4.89, 95% CI (2.65, 9.02); p<0.01]. Furthermore, observed adverse effects included Anemia [OR=0.53, 95% CI (0.26, 0.79); p<0.01], Neutropenia [OR=0.43, 95% CI (0.20, 0.68); p<0.01], and Thrombocytopenia [OR=0.28, 95% CI (0.18, 0.43); p<0.01].ConclusionsToripalimab, being China’s first domestically developed anti-tumor PD-1 antibody drug, shows potential advantages over traditional chemotherapy in possibly prolonging patients’ survival times. However, the limited number of studies included indicates the need for additional single-arm and RCT studies to further validate these findings.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/, identifier (CRD42024519806).